2019
DOI: 10.1371/journal.pone.0220178
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of tocilizumab: A systematic review and network meta-analysis

Abstract: Objectives Our objective was to compare the cardiovascular safety of tocilizumab and other biological disease-modifying antirheumatic drugs (bDMARD) in rheumatoid arthritis using a network meta-analysis (NMA). Methods A systematic literature search through May 2018 identified randomized controlled trials (RCT) or observational studies (cohort only) reporting cardiovascular outcomes of tocilizumab (TCZ) and/or abatacept (ABA) and/or rituximab (RTX) and/or tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 58 publications
0
41
0
3
Order By: Relevance
“…Similarly, there is a theoretical risk of thrombosis with tocilizumab since it alters the lipid profile. However, metaanalysis has shown that it may have better cardiovascular safety as compared with other biological DMARDs [170].…”
Section: Antirheumatic Drugs For Preventing Thrombosismentioning
confidence: 99%
“…Similarly, there is a theoretical risk of thrombosis with tocilizumab since it alters the lipid profile. However, metaanalysis has shown that it may have better cardiovascular safety as compared with other biological DMARDs [170].…”
Section: Antirheumatic Drugs For Preventing Thrombosismentioning
confidence: 99%
“…Second, evidence from observational studies using mouse models supports the role of tocilizumab in treating IS [52][53]. However, this has not been con rmed using RCTs, although RCT evidence found no increased risk of adverse cardiovascular events among RA patients treated with tocilizumab compared with those receiving other biological disease-modifying antirheumatic drugs [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Although tocilizumab significantly increases cholesterol levels and blood pressure, a recent network meta-analysis found the cardiovascular risk with tocilizumab was comparable with other disease-modifying antirheumatic drugs. 44 Regardless, given the high mortality rate among patients with COVID-19-mediated ARDS (.50%), the potential benefits of short-term tocilizumab use seem to outweigh risks of treatment for most patients.…”
Section: Immune Modulatorsmentioning
confidence: 99%